Experimental and regression analysis of chicken feather-based chopped glass fibre mat hybrid composites - Lokesh K S; Shrinivasa Mayya D; Santhosh Kumar T C; Somaiah K S; Sharath Chandra H S; Varun Kumar K R; Sneha; Pavan Kumar P M (Results in Engineering)
The Present work aims to utilize waste chicken feather as reinforcement to develop composites with reduced synthetic fibres in different fractions. Chicken feather (CF) was incorporated at different weight percentage from no feather to 5%,10% and 15% which were manually hybridized with chopped glass fibre (GF) to develop composites designated as GF/CF0, GF/CF5, GF/CF10, and GF/CF15 respectively. Compressed Composite plates were then evaluated for tensile, flexural and impact properties and compared to composites without chicken feather. A free vibration study was also conducted to assess the damping characteristics of hybrid composites. Results indicate that addition of chicken feather significantly alters the mechanical and vibration characteristics. It was observed that GF/CF10 exhibited 120% and 91% higher tensile and flexural strength respectively than GF/CF15 composite due to improper fiber disperssion caused by increased feather content within the matrix. Notably, Impact strength of GF/CF10 composite was nearly 56 % higher than that of neat composites. Adding 15wt.% of CF lowers the mechanical properties with reduced natural frequency due to agglomeration. Regression analysis was performed on tensile and flexural test data to determine the best fit curve using the experimental results. It was found that polynomial regression model of cubic order correlates well with experimental data, yielding the regression coefficient(R2) value of 99.99 %. SEM analysis was done to understand the fracture mechanism of the tested samples. Developed composites featured as sustainable green composites suitable for panel components and used as alternative to wood & plastic composites for light weight applications.